Compounding Institutional Exclusion and Harm: A case study of federally funded Alaskan anti-trafficking service providers - Rothchild, Tatiana; Banks, Ajela; Burns, Tara (Anti-Trafficking Review, 2024)
Federal funds for human trafficking victim programmes and services in the United States have increased from approximately USD 10 million in 2002 to more than USD 90 million in 2022. This increase in fund availability, however, has not necessarily translated into meaningful or accessible services for trafficking survivors. This paper examines the distribution of Department of Justice anti-trafficking funds through the Office for Victims of Crime (OVC), particularly looking at OVC recipients in Alaska. It highlights certain trends in OVC funding in the state, including changes in funding distribution, the emphasis on task force creation and collaboration between service providers and law enforcement, and discussions of equity and inclusion. The paper further explores institutional mechanisms of exclusion and harm of some victims, complexities in collaborating with law enforcement, criminalisation of trafficking survivors, and criteria to qualify for services. As the reality faced by trafficking survivors does not always align with OVC narratives, these mechanisms are illustrated through the experiences of a sex trafficking survivor who has been turned away as not qualifying for services by many of the OVC funded providers in Alaska. The paper concludes by exploring the implications of this research for policymakers and service providers.